1991
DOI: 10.1017/s0950268800056466
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter diarrhoea and an association of recent disease with asymptomatic shedding in Egyptian children

Abstract: SUMMARYA hospital-based case-control diarrhoea survey was conducted in Cairo, Egypt to determine the age-specific frequency of campylobacter infection among diarrhoeic and non-diarrhoeic children aged new born to 5 years. Campylobacter was the most common bacterial enteropathogen isolated from diarrhoeic stools. The overall prevalence of campylobacter isolations was 25 9 % from stools of 143 diarrhoeic children compared to 152 % of 132 non-diarrhoeic control children (P = 0 028) during the 4-month period of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…The ability to avoid the immune response of the host provides an advantage in establishing colonization by C. jejuni, be it as a commensal in animals or as a pathogen in humans. Moreover, asymptomatic infection by C. jejuni is common among children in the developing world, and acute infections are frequently followed by periods of asymptomatic shed- ding (51)(52)(53), which may be due, at least in part, to the ability of this pathogen to avoid the host immune response. Similarly, recrudescence of infection following appropriate antibiotic treatment in an immunocompetent adult has been reported (54).…”
Section: Fig 4 Il-17 Expression Is Reduced In Small Intestinal Cd4mentioning
confidence: 99%
“…The ability to avoid the immune response of the host provides an advantage in establishing colonization by C. jejuni, be it as a commensal in animals or as a pathogen in humans. Moreover, asymptomatic infection by C. jejuni is common among children in the developing world, and acute infections are frequently followed by periods of asymptomatic shed- ding (51)(52)(53), which may be due, at least in part, to the ability of this pathogen to avoid the host immune response. Similarly, recrudescence of infection following appropriate antibiotic treatment in an immunocompetent adult has been reported (54).…”
Section: Fig 4 Il-17 Expression Is Reduced In Small Intestinal Cd4mentioning
confidence: 99%
“…One possibility is that this population may have greater immunity to Campylobacter . Immunity to Campylobacter has been established both in young children in developing countries [38,39,40] as well as with the consumption of raw milk [41]. It is not clear from FoodNet data whether African American children have greater rates of campylobacteriosis than children of other races and ethnicities, which may result in immunity among the African American population.…”
Section: Incidence Rates Of Foodborne Illness Among Low Socioeconomentioning
confidence: 99%
“…Chickens can be colonized with as many as 10 9 CFU C. jejuni per gram cecal contents (43), and colonized mice can shed up to 10 6 CFU per mg feces (18). Studies of children in developing countries have shown that rates of asymptomatic carriage of Campylobacter in children are around 15% (108,131), suggesting that some acquired immunity is induced from multiple exposures during early childhood. Wheeler et al reported a rate of asymptomatic carriage of 0.7% in a population study involving adults in the United Kingdom (179).…”
Section: Pathology and Pathophysiology Of Campylobacter Infectionmentioning
confidence: 99%